SISTEM PENTANAHAN SWITCHYARD DENGAN KISI-KISI (GRID) PADA GARDU INDUK 150 KV BANTUL - Hani, Slamet (IST AKPRIND YOGYAKARTA, 2017)
The substation has a great possibility of experiencing a hazard caused by the disturbance of lightning and overcurrent so that the current disturbance flows to the ground as a result of the insulation of equipment that is not functioning properly. One of the security systems on the substation is grounding. The grounding system is a delivery system that connects the system, equipment and installation bodies with the earth / ground so as to secure the human from electric shock, and secure the installation components from the dangers of abnormal voltage / currents. Therefore, research is conducted with respect to the grid earthing system on the Switchfield Substation (GI) switchyard. The research applies some data retrieval methods, namely: Literature study method, covering the studying literature related to earth system in switchyard area of 150 kV Bantul, and litrature related to earth type resistance calculation, soil type resistance, type of system earth, and type of electrode used. Based on the result of the analysis of the value of ground grid of Substation in Bantul is 0,527 Ohm. Or the difference in value of 0.043 Ohm or 7.54% smaller than the measurement value of 0.57 Ohm. Touch tension value of 207.5 Volts for people weighing 70kg, and 153.3V for weight 50Kg. with the actual maximum touch voltage value of 261.53 Volts. The step voltage value of 288.7 Volts for people weighing 70kg, and 213.3V for weight 50Kg. with an actual maximum step voltage value of 857.4 Volts.